2021
DOI: 10.3390/su132312956
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Perspective for Understanding Digital Transformation in Higher Education: Overview and Subregional Context in Latin America as Evidence

Abstract: Since virtual education has increased from a local to a global audience, it is of great importance to understand the role that cultural and social backgrounds play in the transition to digital education. Therefore, a review of preferences and evidence among different Latin American regions and nations increases understanding. This digital transformation can be assessed under several categories of cultural, social, and economic situations. Traditionally, universities are known as formal institutions with emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
0
15
0
4
Order By: Relevance
“…A retrospective on the digitization process in Latin American and Caribbean countries shows that, prior to the pandemic, ICT in education has focused on disruption and innovation. This includes the incorporation of operational activities with a creative sense, such as augmented reality, machine learning, and video games [88].…”
Section: Presence Of Ict In Latin American Universitiesmentioning
confidence: 99%
“…A retrospective on the digitization process in Latin American and Caribbean countries shows that, prior to the pandemic, ICT in education has focused on disruption and innovation. This includes the incorporation of operational activities with a creative sense, such as augmented reality, machine learning, and video games [88].…”
Section: Presence Of Ict In Latin American Universitiesmentioning
confidence: 99%
“…In addition to this digital divide, professors in Latin America and the Caribbean have had to face other problems linked to the geographical characteristics of their region, as it is very extensive in terms of territory and population, with a high dispersion of the population and unequal access to technological resources [ 28 ]. This has resulted in difficulties in providing education during the pandemic due to the generalized socioeconomic differences among students, caused by unequal access to technology, connectivity, and digital resources [ 29 ]. Finally, the digital competencies developed by professors, conditioned by their experience in the use of ICT, have been shown to be insufficient or improvable [ 30 ], and it was also observed that inequalities in the use of digital skills by professors were conditioned by gender or age [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained also allow to assume that professors in Latin American private universities have, in general, better self-concepts of their digital competence than professors in public universities, and they also value better than the latter the professional aspects linked to the digitalization of higher education ( Table 4 ). Private universities in the Latin American region probably have a higher proportion of distance students than public universities, which may explain why they make a greater digitization effort, both in terms of equipment and faculty training [ 14 , 15 ]. This would justify the fact that both the results obtained here and those of other studies systematically show that professors at private universities claim to have better digital skills than those at public universities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, COVID-19 evidenced the need to provide relevant, interactive, and user-friendly digital teaching resources and content, constituting a turning point in the development of online content in the classroom [ 29 ]. Most studies related to digital transformation in higher education focus on the need to strengthen digital strategies to reinforce the use of technologies as part of the digital agenda in Latin America and the Caribbean [ 14 ]. In this task, university professors and the digital competencies that this task requires are directly involved.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation